ZnO-TiO2 Composite Mediated Photocatalytic Degradation of Orange G from Aqueous Solution - Hossain, Farhana; Rahman, Md Ataur; Hossain, Md Mufazzal (Dhaka University Journal of Science, 2022)
Composites of ZnO-TiO2 with different ratios have been prepared by heating the mixtures at different temperatures and characterized by SEM, FT-IR and XRD techniques. The results from these techniques support the formation of the composites. These composites have been applied for photodegradation of a textile dye, orange G (OG). The composite with a composition of ZnO:TiO2 = 75:25 prepared at 500 oC has been found to show the highest catalytic efficiency. The experiments have been carried out by varying the experimental conditions to optimize them. The best catalytic performance has been found with 0.25 g/100 mL of the catalyst, 1.02× 10-4 M initial concentration of OG and the UV light source. A mechanism for photocatalytic degradation of dye has been proposed. Dhaka Univ. J. Sci. 69(3): 218-224, 2022 (June)